Rewiring corporate law for an interconnected world - Enriques, L; Romano, A (University of Arizona, 2022)
The traditional focus of corporate law is on aligning managers’ preferences to the interests of shareholders. This view is premised on two assumptions that are no longer true: first, the idea that all shareholders want to maximize the net present value of the firm’s earnings per dollar invested; and, second, the view that microeconomic shocks do not produce macroeconomic consequences. The rise of institutional investors undermines the first assumption, since large asset managers hold the entire market and have been shown to display a preference for maximizing the value of their portfolio as a whole, with limited interest in the performance of specific companies: that is, they are “portfolio value maximizers.” At the same time, the increasingly interconnectedness of the economy, and society more broadly, undermines the second assumption, as there is ample empirical evidence demonstrating that microeconomic shocks can propagate through the existing interconnections and generate catastrophic consequences. We also show how a subset of firms, those “central” to the network of interconnections that comprises the economy, is responsible for those shocks. We argue that corporate law should reflect these features of contemporary economies, and hence change its fundamental purpose. On the one hand, it should aim to ensure that non-central firms maximize their own value, despite the rise of portfolio value maximizers. On the other hand, in central firms it should harness the preferences of portfolio value-maximizing shareholders with the goal of minimizing the risk of catastrophic externalities like climate change or financial crises. We develop a framework to guide policymakers in the pursuit of this new fundamental conception of corporate law and provide concrete examples of how changes in the rules on dual class shares, tenure voting, and ownership disclosure could account for these changes.